Penentuan Dalam Pemilihan Ekspedisi Menggunakan Metode Analytic Processes Network dan Dynamic Programming - Ardiansyah, Moch Fajar; Wulandari, Indah Apriliana Sari (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
An expedition or delivery service is a transportation equipment rental service to move goods or people. PT IPP is a company that operates in the field of product packaging printing. In the delivery process, errors often occur in the process of selecting the type of truck to be used. Based on data from July to November 2023, there were several errors in selecting transportation equipment (type of truck). These errors result in several products being delayed, the production process being hampered and can result in employees working overtime, so this research is aimed at selecting the type of transportation used according to the criteria. The criteria required range from weight capacity to product quantity capacity and the selection of expedition services that have the type of transportation equipment that suits the product cubication. Data processing uses the Analytic Network (ANP) method to recommend expedition services to be used in product delivery and the dynamic programming method to fulfill vehicle capacity. The results obtained are that the most dominant criterion is price with the highest percentage value of 24% and the most dominant alternative for selecting expedition services is Barokah Tani with the highest percentage value of 10%. The results of the dynamic programming method are that the largest value of f2(y) is for a truck with a capacity of 54m3 which can load two products, namely products C and B, while for product A you can use a truck with a capacity of 18m3.